Multifunctional sequence-defined macromolecules for chemical data storage - Steven Martens (Nature Portfolio, 2018)
Sequence-defined macromolecules consist of a defined chain length and topology and can be used in applications such as antibiotics and data storage. Here the authors developed two algorithms to encode text fragments and QR codes as a collection of oligomers and to reconstruct the original data.